2019
DOI: 10.1016/j.jgr.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Glomus intraradices on the physiological properties of Panax ginseng and on rhizospheric microbial diversity

Abstract: BackgroundGlomus intraradices is a species of arbuscular mycorrhizal fungi that, as an obligate endomycorrhiza, can form mutually beneficial associations with plants. Panax ginseng is a popular traditional Chinese medicine; however, problems associated with ginseng planting, such as pesticide residues, reduce the ginseng quality.MethodsIn this experiment, we studied the effect of inoculating G. intraradices on several physiological properties and microbial communities of ginseng. UV-Visible Spectrum method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…The beneficial microbiota, containing AMFs, PGPBs, and PGPFs, also affects the metabolism of various substances in plants [10,106,107]. This mutual relationship between microbiota and plants effectively supports plant performance and resistance to adverse environmental conditions [8][9][10][11] (Figure 1b).…”
Section: Why Plants Need Beneficial Microbiotamentioning
confidence: 97%
See 4 more Smart Citations
“…The beneficial microbiota, containing AMFs, PGPBs, and PGPFs, also affects the metabolism of various substances in plants [10,106,107]. This mutual relationship between microbiota and plants effectively supports plant performance and resistance to adverse environmental conditions [8][9][10][11] (Figure 1b).…”
Section: Why Plants Need Beneficial Microbiotamentioning
confidence: 97%
“…Furthermore, one study reported that selenium (Se) × AMF interactions promoted both soybean and forage grass (Urochloa decumbens) for Se absorption, which improved the quality of the two plants used as animal feed [87]. Rhizoglomus intraradices, one model species of AMFs, help rice, soybean, ginseng (Panax ginseng), and other crops resist drought and cold stresses and promote nutrient absorption [10,88,89]. R. intraradices also promoted rice plants to resist blast disease (caused by Magnaporthe oryzae spores), and the transcriptome data revealed that R. intraradices-inoculated rice plants exhibited significantly higher expression levels of genes related to the auxin and salicylic acid signaling pathways than the noninoculated rice plants in response to M. oryzae [11].…”
Section: Plant Growth-promoting Fungimentioning
confidence: 99%
See 3 more Smart Citations